Kadar Protein, Seng, dan Nilai Ekonomi Gizi Muffin dengan Substitusi Tepung Kecambah Kacang Tunggak (Vigna unguiculata) yang Diperkaya Serbuk Wijen (Sesamum indicum - Hisma Zauharotun Nisa; Annis Catur Adi (Media Gizi Kesmas, 2023)
Background: Deficiency of macronutrients and micronutrients in school-age children is still a nutritional problem that is often found in Indonesia. Many Indonesian children with protein and zinc intake do not meet the recommended daily allowance. Cowpea is a source of protein and a type of legume that is often found in Indonesia. Sesame is a source of protein and zinc which is cheaper than other zinc sources. Both of these ingredients have the potential to be substitutes and additions to muffins as a nutrient-dense snack for school-age children. Objectives: To develop muffins with germinated cowpea flour substitutes enriched with sesame powder to increase the nutritional content of protein and zinc muffins, as well as to determine the nutritional economic value of this product. Methods: This study was an experimental study with a Completely Randomized Series design with three treatments: control formula (F0), formula F2 (15 grams of cowpea sprout flour and 15 grams of sesame powder), F3 formula (30 grams of cowpea sprouts flour and 20 grams of sesame powder). grams). Protein and zinc levels were obtained from nutritional analysis, while the economic value per unit of nutrition was obtained from calculating the food cost divided by nutrient content. Results: The results of the nutritional analysis showed that there was an increase in nutrient levels in formulas F1 and F2, with the highest levels of protein and zinc obtained by F2 (7.64 grams of protein and 1.862 milligrams of zinc per 100 grams). All formulas except F0 were able to meet the adequacy of protein snack foods and all formulas were able to meet the adequacy of zinc in snack foods for school-age children. The economic value per unit of nutrient shows the cheapest protein and zinc prices obtained by formula F2 with a protein price of IDR 457/g and a zinc price of IDR 2057/mg Conclusions: The substitution treatment of cowpea sprout flour and the addition of sesame powder was able to increase the protein and zinc content in muffins making them suitable as an alternative nutrient-dense snack for school-age children. This treatment also makes muffins have cheaper protein and zinc prices per unit of nutrition.